F(x) = 4x - 9
let f(x) = y, this implies that x = f⁻¹(y)
y = 4x - 9 Let us solve for x.
4x - 9 = y
4x = y + 9
x = (y + 9)/4
Recall that x = f⁻¹(y),
x = (y + 9)/4
f⁻¹(y) = (y + 9)/4
That means that for f⁻¹(x)
f⁻¹(x) = (x + 9)/4
Hope this explains it.
Answer:
2
Step-by-step explanation:
consider the two points. Gradient=change in y/change in x. So 4/2=2
Use Pythagorean theorem to solve.
a^2 + b^2 = c^2
6^2 + b ^2 = 14^2
36 + b^2 = 196
Subtract 36 from both sides.
b^2 = 196-36
b^2 = 160
Take the square root of both sides.
b = sqrt 160
As a decimal
b = 12.649
As a simplified radical
b = 4sqrt10
Answer:
$6.20 is the cost of candy per pound.
5/31 lbs of candy would be for $1.
Step-by-step explanation:
Full Answer.
If the triangle is an equilateral triangle, then all three angles are exactly 60 degrees each. A right-angled triangle has one angle of 90 degrees, which is the right angle, with two more angles that total 90 degrees when added together.